Elavl1 deletion in limb mesenchyme is dispensable for skeletal morphogenesis - Parsha, Rohini; Kota, Satya K. (Frontiers in Cell and Developmental Biology, 2025)
Embryonic lethal abnormal vision-like protein 1 (Elavl1)/human antigen R (HuR) is an RNA-binding protein implicated in multiple developmental processes, with pleiotropic roles in the RNA life cycle. Early embryonic loss of Elavl1 in epiblast cells is lethal due to defects in placental branching and embryonic tissue growth. Postnatal global deletion of Elavl1/HuR results in lethality with atrophy in multiple tissues, mainly due to the loss of progenitor cells. However, the roles of Elavl1 specifically during embryonic limb skeletal development are not well understood. In this study, we report that the deletion of Elavl1 in limb bud mesenchyme in mice did not reveal any abnormalities during embryonic development, with normal development observed in pre- and postnatal limb skeletons. Analyses of skeletal patterning, morphogenesis, and skeletal maturation, including skeletal elements in the stylopod, zeugopod, and autopod, during development did not reveal any significant differences between long bones from control and Elavl1 conditional knockout (cKO) animals. Our study indicates differential dependency and susceptibility to the loss of Elavl1 in different stem cell lineages, with its functions being dispensable during limb skeletal development.